Downregulation of GEP100 Improved the Growth Inhibition Effect of Erlotinib Through Modulating Mesenchymal Epithelial Transition Process in Pancreatic Cancer. Issue 6 (July 2018) - Xie, Chuan-gao; Sun, Shi-long; Wei, Shu-mei; Xu, Xiao-ming; Shao, Li-ming; Chen, Jia-min; Cai, Jian-ting
Abstract : Objective: The epidermal growth factor receptor is overexpressed in the majority of pancreatic cancer. Epidermal growth factor receptor tyrosine kinase inhibitor erlotinib was approved to treat patients combining with gemcitabine. However, the sensitivity is low. Here, we try to reveal the regulatory role of guanine nucleotide exchange protein 100 (GEP100) in erlotinib sensitivity. Methods: We investigated the correlation between GEP100 expression and sensitivity to erlotinib in different pancreatic cancer cell lines, followed by examination of the effect of GEP100 on erlotinib sensitivity by establishing the stable knocked-down cell line. The expression level of epithelial mesenchymal transition–related protein was examined by Western blot, and the regulatory mechanism was investigated by short hairpin RNA. Xenograft experiment was also performed in nude mice. Results: We identified a significant correlation between sensitivity to erlotinib and expression of GEP100. GEP100 downregulation increased its sensitivity to erlotinib. E-cadherin short hairpin RNA treatment inhibited this sensitivity. Immunohistochemical staining showed a mutual exclusive expression pattern of GEP100 and E-cadherin in human pancreatic cancer tissues. Xenograft showed that downregulation of GEP100 enhanced the growth inhibition of erlotinib in nude mice. Conclusions: Our results suggested that GEP100 and E-cadherin have the predictive value for responsiveness to erlotinib in pancreatic cancer.